Public procurement fundamentals : lessons from and for the field (includes a simple step-by-step generic procurement manual) - Khan, Naushad (Emerald Publishing Limited, 2018)
During the last two decades, public procurement evolved in most of the world but is often carried out by government officials with little or no experience with procurement policies and procedures. As a result, substantial amounts of public funds are lost due to wrong selection of suppliers and contractors. While a large amount of literature exists on public procurement, it deals with different aspects such as commercial, environmental, legal, and technical aspects. In this new work, Khan provides an introduction to procurement and efficiency, bringing together these difficult and complex aspects of public procurement in a clear and succinct manner. From his experience with the World Bank throughout Central and Eastern Europe, Balkans, Caucuses, and Central and South Asia, Khan has created a step-by-step manual for government officials, researchers, and students.
Includes index.
Keywords: Government purchasing.; Political Science -- Political Economy.; Public finance.; elektronické knihy; electronic books